Hygroscopic equilibrium time dependence of stability characteristic angles in granular media - Gomez Arriaran, I. (2025)
The characteristic angles of the granular media depend on such grain parameters as size, geometry and roughness, as well as the degree of packing fraction or compactivity, and the relative humidity within the medium. In this work, we study the relationship between the characteristic angles and time during which the granular medium is stored in a humidity controlled environment, for grains of different geometry.The characteristic angles were experimentally measured for successive avalanches of grain packings with spherical and irregular geometries under conditions of varying relative humidity (75 % - 84 % - 94 %). It was found that, for each grain geometry and determined relative humidity, there is a time at which the angle of maximum stability becomes constant. This time will be referred to as the “characteristic stability time” or “hygroscopic equilibrium time” (th), which is governed by the moisture diffusivity within the granular packing.It is shown that, for the same grain geometry, the angle of repose is independent of the characteristic time and therefore of the relative humidity. It was found that, for irregular geometry grains, the angle of maximum stability increases with higher relative humidities (showing an increase of 7° from 75 % to 94 % relative humidity). For spherical beads, the angle of maximum stability remains smaller than that of irregular ones, from 75 % to 84 % relative humidity. However, at very high relative humidity (94 %), it increases abruptly in comparison to irregular grains, indicating that the cohesive forces between grains is smaller for irregular grains than for spherical grains.